Sleep duration during the school week is associated with C-reactive protein Risk Groups in healthy adolescents - Hall, Martica H. (Sleep Med, 2014)
BACKGROUND: The prevalence of short sleep duration in adolescence and the relevance of early risk factors to cardiovascular disease in adulthood suggest that adolescence is an opportune time to evaluate links between sleep duration and cardiovascular disease risk. We examined associations among actigraphy-assessed sleep duration and sleep debt with elevated C-Reactive Protein (CRP), a known risk factor for cardiovascular disease. METHODS: Participants were 244 (137 Blacks, 116 males) healthy high school students, each of whom wore wrist actigraphs for one week and provided a fasting blood draw. CRP was examined as both a continuous and categorical outcome, with CRP > 3 mg/L identifying a High Risk Group. RESULTS: Sleep duration and sleep debt were significantly associated with CRP High Risk Group in covariate-adjusted analyses. Shorter sleep duration on school nights was associated with a greater likelihood of being in the High Risk CRP Group. Likelihood of being in the High Risk CRP Group was doubled in students who obtained an average of two or more hours of “catch up” sleep on weekend nights. CONCLUSIONS: Reduced weekday sleep duration and sleep debt were both associated with CRP Risk Group in adolescence. That these relationships may be observed prior to the onset of clinical disease suggests that adolescence may provide an opportune period for disease prevention.